3. TELEVISI LOKAL DAN KAMPANYE TERSELUBUNG CAGUB-CAWAGUP PILKADA JATENG 2008 - Hasfi, Nurul (Faculty of Social and Political Sciences Diponegoro University, 2008)
Veiled campaign run by mass media is a phenomenon that can not be separated from almost all general election, including Central Java Governor Election 2008. Some local televisions in Semarang, for example, are used by candidates to employ this kind of â€œillegalâ€ campaign. It is automaticaly emerging negative atmosphere in the process of democracy during the general election. Indonesian Broadcasting Committee of Central Java (KPID Jateng) that has role to control local televisionâ€™s activities in broadcasting the general election, has legalized regulation no 01 year 2008. The decre provides clear devinision of political campaign, governor election socialization and also the veiled campaign. Unfortunately the veiled campaigns aired by local television are still â€œkeep on its tractâ€ since the rule is not obeyed by local television and is not applied complitely by KPID.